Institutional Strengthening and Improvement of National Logistics Performance Through The Establishment of A National Supply Chain Agency - Setiawan, R. Beniadi (Syntax Literate, 2024)
The logistics sector has a very important role in driving Indonesia's economic growth. However, the national logistics system currently faces various obstacles that prevent it from reaching its full potential. Many challenges slow down the development of this sector. To overcome these obstacles, it is necessary to strengthen institutions that are able to integrate and optimize logistics performance throughout Indonesia. This research suggests the establishment of a National Supply Chain Agency as a solution to improve the coordination, efficiency, and effectiveness of the logistics system. The purpose of this study is to identify and evaluate the role and impact of the establishment of the National Supply Chain Agency on improving national logistics performance. This research uses a qualitative method with data collection from literature studies. The collected data were then analyzed through the stages of filtering, presenting, and drawing conclusions. The results showed that the establishment of the National Supply Chain Agency is an important step to improve logistics performance in Indonesia. The agency is expected to address current challenges, such as inefficiency, high logistics costs, and distribution delays. Thus, the National Supply Chain Agency is proposed as a solution to improve the competitiveness of national logistics, both in the domestic and international markets, and contribute to sustainable economic growth.